2015
DOI: 10.1007/bf03379620
|View full text |Cite
|
Sign up to set email alerts
|

Current Situation and Clinical Characteristics of Sedative-Related Disorder Patients in Japan: Comparison with Methamphetamine-Related Disorder Patients

Abstract: The purpose of the present study is to examine the current situation of sedative-related disorders (mainly benzodiazepines) in Japan and the clinical characteristics of Japanese patients with this disorder. Subjects were 671 drug-related disorder patients diagnosed according to the ICD-10 classification as "F1: mental and behavioural disorders due to psychoactive substance use," who abused psychoactive substances other than alcohol. Of all the psychiatric hospitals in Japan between September and October 2010, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…This study also confirmed that the educational background of DDRD patients was higher and the relationships with antisocial groups lower than MARD patients and, as such, this type of lifestyle background has more in common with HARD patients. These findings are consistent with our previous study . The above suggests the possibility that designer‐drug abuse has spread from the center of a class with a relatively general lifestyle background of young men who are also not antisocial.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study also confirmed that the educational background of DDRD patients was higher and the relationships with antisocial groups lower than MARD patients and, as such, this type of lifestyle background has more in common with HARD patients. These findings are consistent with our previous study . The above suggests the possibility that designer‐drug abuse has spread from the center of a class with a relatively general lifestyle background of young men who are also not antisocial.…”
Section: Discussionsupporting
confidence: 93%
“…At first, DDRD patients were younger than both MARD and HARD patients and the proportion of men was higher. This study has also confirmed our previous report 13 that the proportion of men was overwhelmingly higher among MARD than HARD patients. However, the proportion of men was even higher among the DDRD patients than the MARD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, drug dependence caused by abuse of prescription drugs is increasing in Japan. According to a nationwide psychiatric hospital survey, the proportion of patients with sedative (mainly benzodiazepine)‐related disorders has more than doubled in the last decade …”
mentioning
confidence: 99%